2019
DOI: 10.1002/ijc.32486
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer mortality reduction by LDCT screening—Results from the randomized German LUSI trial

Abstract: In 2011, the U.S. National Lung Cancer Screening Trial (NLST) reported a 20% reduction of lung cancer mortality after regular screening by low‐dose computed tomography (LDCT), as compared to X‐ray screening. The introduction of lung cancer screening programs in Europe awaits confirmation of these first findings from European trials that started in parallel with the NLST. The German Lung cancer Screening Intervention (LUSI) is a randomized trial among 4,052 long‐term smokers, 50–69 years of age, recruited from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
266
3
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 325 publications
(293 citation statements)
references
References 18 publications
7
266
3
17
Order By: Relevance
“…This study represents a timely and important update to the NLST data, alongside full results of the NELSON [7] and the LUSI trials [8], as Europe begins to set out a vision for LC screening. Although 10 years have passed since the publication of the first results of this landmark study, the USA still encounters the difficulties of implementation and the challenges of screening uptake by highrisk populations.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…This study represents a timely and important update to the NLST data, alongside full results of the NELSON [7] and the LUSI trials [8], as Europe begins to set out a vision for LC screening. Although 10 years have passed since the publication of the first results of this landmark study, the USA still encounters the difficulties of implementation and the challenges of screening uptake by highrisk populations.…”
Section: Commentarymentioning
confidence: 99%
“…The NLST also supports evidence implied by the European screening trials that there is a sex difference in the benefit of LC screening in favour of females, which the NELSON trial could not fully address given most participants were male [7]. In addition, the German LUSI trial found that LDCT screening led to a statistically significant reduction in LC mortality among women (hazard ratio (HR) 0.31, p=0.04), but not among men (HR 0.94, p=0.81) [8]. This is an area that future studies will need to address to determine whether LC screening needs to be stratified by sex.…”
Section: Commentarymentioning
confidence: 99%
“…In over 15,000 patients with incidental nodules from a commercial insurance database, only 36% received subsequent workup despite an estimated cost of only $1-$2 per member per year when averaged across the insured population [7]. Lung cancer screening in appropriate patients has increased earlystage detection (36-71% Stage I) [8] and reduced long-term mortality rates [9][10][11][12]. However, as with incidentally detected nodules, false positive rates are high [9].…”
Section: Introductionmentioning
confidence: 99%
“…Dies ist in der täglichen Praxis auch für die Einordnung der Noduli in die geltenden Empfehlungen der Fleischner-Society und die damit verbundenen Handlungsempfehlungen hilfreich [3]. Die prinzipiell durch die Studienautoren thematisierte Herausforderung, nämlich die klinische Einordnung (inzidenteller) Findings in der thorakalen Bildgebung, wird sicher an Relevanz gewinnen, nicht zuletzt, sollten Lungenkrebs-Screenings auch in Deutschland eingeführt werden [4].…”
unclassified